Imperfect Competition in Audit Market and its Effect on the Demand for Audit-Related Services. - Gigler, Frank; Penno, Mark (The Accounting Review, 1995)
Looks at the effect of imperfect competition in audit markets on the demand for audit-related services. Switching costs; Effect on structure of audit engagement structure and client-auditor relationship; Audit pricing; Low-balling; Auditor switching.